Enterosorbents in complex therapy of food allergies: a focus on digestive disorders and systemic toxicity in children - Shichkin, Valentin P.; Kurchenko, Oleg V.; Okhotnikova, Elena N.; Chopyak, Valentyna V.; Delfino, Domenico V. (Frontiers in Immunology, 2023)
The review analyzes mechanisms and concomitant factors in developing IgE-associated allergic diseases provoked by food allergens and discusses clinical symptoms and current approaches for the treatment of food allergies. The expediency of using enterosorbents in complex therapy of food allergies and skin and respiratory manifestations associated with gastroenterological disorders is substantiated. The review summarizes the experience of using enterosorbents in post-Soviet countries to detoxify the human body. In this regard, special attention is paid to the enterosorbent White Coal (Carbowhite) based on silicon dioxide produced by the Ukrainian company OmniFarma.